دراسة قابلية الخلايا اللمفاوية التائية على التحول و الأنقسام في المرضى المصابين بألتهاب المفاصل الرثوي و داء الذئب الأحمراري - رحمن, سناء; رحمن, هناء; صادق, غنيمة (Al-Nahrain Journal of Science, 2018)
T-Lymphocytes transformation is considered one of the cellular immune response aspects for that we studied this process in patients with Rheumatoid Arthritis (RA) and Systemic Lupus Erythematosus (SLE) by using phytohaemagglutinin (PHA) as mitogen, the results was showed asignificant reduction (P